Badis britzi, a new percomorph fish (Teleostei: Badidae) from the Western Ghats of India - Dahanukar, Neelesh; Kumkar, Pradeep; Katwate, Unmesh; Raghavan, Rajeev (Zootaxa, 2015)
Badis britzi, the first species of the genus endemic to southern India, is described from the Nagodi tributary of the west-flowing Sharavati River in Karnataka. It is distinguished from congeners by a combination of characters including a slender body, 21–24 pored lateral-line scales and a striking colour pattern consisting of 11 bars and a mosaic of black and red pigmentation on the side of the body including the end of caudal peduncle, and the absence of cleithral, opercular, or caudal-peduncle blotches, or an ocellus on the caudal-fin base. Badis triocellus Khynriam & Sen is considered a junior synonym of B. singenensis Geetakumari & Kadu.